Computer technology and information retrieval in Nigeria (1994)
Computer technology, though still advancing in developed countries, is still in its infancy in Nigeria. The benefits of this technology are highlighted and its potential as a fast and easy way of communication globally is undiputed. How can Nigeria benefit from this technology? Some of the problems of introducing this new technology and actually making it work are discussed.